Voice Over Internet Protocol Performance Evaluation in 6to4 Tunneling Network - Hirzan, Alauddin Maulana; Bahaman, Nazrulazhar; Adhiwibowo, Whisnumurti (Jurnal Transformatika, 2020)
Registry reported that their regional already in exhausted state. The IPv6 was proposed to substitute IPv4 network, but the implementation of this version cased many problems such as hardware compatibility. As temporary solution to this problem, 6to4 tunneling transition mechanism is introduced as one of many solutions. This mechanism used IPv4 network as communication media between two IPv6 networks. Thus, this kind of mechanism will affect the performance of Voice over Internet Protocol. VoIP demanded real-time communication by using UDP protocol between nodes. Unlike normal communication mode, real-time mode required data to be sent immediately ignoring the quality of data. This research evaluated the performance of 6to4 tunneling mechanism for Voice over Internet Protocol s communication between two nodes in native IPv6 networks.
Keywords: VoIP; 6to4 Tunnel; Performance Evaluation; GNS3